THE INFLUENCE OF PAIR CHECKS AND LEARNING CYCLE MODELS TOWARDS COMPREHENSION OF CONCEPT VIEWED FROM LEARNING MOTIVATION OF STUDENTS - Danang Tria Wibowo; Intan Sari Rufiana (EDUPEDIA, 2017)
This study aims to know: (1) Do pair checks and learning cycle models influence to students’ mathematics comprehension of concept. (2) Do high-motivated students have better comprehension of concept than less-motivated and low-motivated students. (3) Do category of students’ motivation of learning cycle model ensue better comprehension of concept than category of students’ motivation of pair checks model. (4) Do high-motivated students’ learning models (pair checks and learning cycle) have better comprehension of concept than less-motivated and low-motivated students. This study is categorized as a quasi-experimental study with factorial design. The population of the study is all seventh grade students of SMPN 1 Balong. Purposive sampling is used to take the sample of study. Data analysis technique applied includes normality test using Liliefors method. Homogeneity test applies Bartlett test. Balance test utilizes T-test. In addition, hypothesis test uses analysis of two-way variance with unequal cells. Thus, it continues with double comparison test with Scheffe method. The result of the study show that (1) pair checks and learning cycle models influence to the students’ comprehension of concepts; (2) high-motivated students have the same comprehension of concept as less-motivated and low-motivated students; (3) those high-motivated students who use learning cycle model have better comprehension of concept that those high-motivated students who use pair checks model. Meanwhile, those less and low-motivated students who use pair checks model have the same comprehension of concept than those less and low-motivated students who use learning cycle models; (4) in each model category (pair checks and learning cycle), high, less, and low-motivated student have no different comprehensionof concept.